Dźwięk [м] na ćwiczeniach z emisji głosu nauczyciela języka rosyjskiego - Zaorska, Magdalena (Przegląd Rusycystyczny, 2014)
Magdalena Zaorska Uniwersytet Warmińsko-Mazurski, Olsztyn, Poland magzaorska@gmail.com ЗВУК [М] НА ЗАНЯТИЯХ ПО ФОНАЦИИ ГОЛОСА ПРЕПОДАВАТЕЛЯ РУССКОГО ЯЗЫКА Резюме Статья посвящена месту, какое занимает звук [м] в работе над техникой речи (ды-хание, фонация, артикуляция) преподавателя русского языка. Автор знакомит читателя с научным мнением сотрудников Кафедры сценической речи Санкт-Петербургской государственной академии театрального искусства относительно упражнений, которые базируются на анализированном звуке. В первой части статьи даётся теоретическое обоснование использования звука [м] в процессе работы над голосом. Во второй части предлагаются дыхательные, фонационные и дикционные упражнения со звуком [м], которые могут быть также использованы на занятиях по практической фонетике русского языка. SOUND [M] IN CLASSES IN THE VOICE PRODUCTION OF THE RUSSIAN LANGUAGE TEACHER Summary The article is devoted to the place, which sound [m] takes in work on the broadly defined speech technique (breathing, phonation, articulation) of the Russian language teacher. The author introduces a scientific opinion of the lecturers of the Voice & Speech Department of Saint Petersburg State Theatre Arts Academy relating to the exercises based on the analysed sound. In the first part of the article a theoretical approach of the use of sound [m] in the process of working on the voice has been presented. In the second part the breathing, voice production and diction exercises with sound [m], which can be used as a material to work on pronunciation in practical phonetics of Russian language, have been proposed.